Criminal Responsibility in Geropsychiatry: Competence, Culpability, and Care. Issue 5 (September 2021) - Pandey, Praveen; Varshney, Prateek; Gajera, Gopi V; Nirisha, P Lakshmi; Malathesh, Barikar C; Manjunatha, Narayana; Sivakumar, Palanimuthu T; Kumar, C Naveen; Math, Suresh Bada
Elderly persons can get involved in the criminal justice system as victims or as perpetrators. The interaction of elderly persons with mental illness at various cross-sections of the judicial process needs thoughtful consideration. Through this review, the authors approach this less studied aspect of forensic psychiatry. Concerning the evaluation of a prisoner, three scenarios need focused consideration: evaluation for fitness to stand trial before a competent court, evaluations for an insanity defense, and fitness for sentencing. At the same time, incarcerated elderly who developed dementia or a severe mental illness at any point of time during the trial or in prison need specific approaches. In this article, the authors discuss the acts and case laws relevant to navigating these legal scenarios. We discuss existing mental health care provisions for protecting the health interests of elderly care in prison.